The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1677-5538.ibju.2013.06.14
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Symptoms and Urodynamics Findings in Patients with Friedreich's Ataxia

Abstract: Purpose: To assess the prevalence of LUTS, urinary tract and urodynamics changes in patients with Friedreich's Ataxia (FA), the most common form of hereditary ataxia. Materials and Methods:This study evaluated 258 patients with genetically confirmed diagnoses of FA. Of the patients, 158 responded to a questionnaire which assessed their urinary symptoms. Patients with clinical changes underwent renal function examinations, ultrasound, and urodynamic studies (UDS). Results: The sample analyzed showed that 82% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…On the other hand, we strengthened our findings by means of an extensive screening procedure and accurate patient characterization in a cohort of genetically confirmed FRDAs. Notably, in most of previous studies potential confounders such as vitamin deficiency or impaired glucose intolerance, which may per se cause an autonomic neuropathy, were not considered [ 10 , 11 , 27 ]. Moreover, the lack of validated scales precluded correlations with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we strengthened our findings by means of an extensive screening procedure and accurate patient characterization in a cohort of genetically confirmed FRDAs. Notably, in most of previous studies potential confounders such as vitamin deficiency or impaired glucose intolerance, which may per se cause an autonomic neuropathy, were not considered [ 10 , 11 , 27 ]. Moreover, the lack of validated scales precluded correlations with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…The urodynamic findings were consistent with larger case-series that have shown detrusor overactivity as the predominant finding, however, only 2 patients had these tests [ 26 , 27 ]. Other findings on urodynamic studies have included detrusor underactivity, detrusor acontractility and detrusor-sphincter dyssynergia [ 14 ]. This would account for the urinary disturbances reported by our patients as there were high scores in OAB indicating detrusor overactivity and LS indicating possible detrusor-sphincter dyssynergia due to pyramidal tract involvement or peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cohorts of FRDA patients have noted complaints of sphincter disturbance or urinary incontinence but this has not been clarified further [ 5 , 10 13 ]. Only one large study of 258 FRDA patients showed that 82% of patients reported LUTS and 22% related these symptoms to poorer quality of life [ 14 ]. Smaller case-series have evaluated LUT function in a select group of patients but this has not been extended to larger groups.…”
Section: Introductionmentioning
confidence: 99%
“…Micturition is only mildly affected with urgency and detrusor hypoactivity being the most frequent symptoms. In a series of FA patients, there was evidence for dilatation of the upper urinary tract without creatinine increase in 14% [16]. Systematic assessment of bowel function has not been published to date.…”
Section: Phenotypementioning
confidence: 99%